Prospects of the auriferous content of the North-Bureya metallogenic zone in Priamurskaya province - V. A. Stepanov; A. V. Melnikov (Известия высших учебных заведений: Геология и разведка, 2016)
It has been established that the North Bureya metallogenic zone is one of the most productive for the mining and alluvial gold in the Priamurskaya province. The total production of ore gold (97 ton) and alluvial gold (160 ton) within the zone was 26,5% of the total gold production in the province. Within North-Bureya metallogenic zone the six ore-placer nodes are allocated - Burindinsky, Umlekansky, Yasnensky, Oktyabrsky, Adamihinsky and Sohatiny. Besides that, the four nodes (Ulunginsky, Tygdinsky, Magdagachinsky and Igaksky) constitute Gonzhinsky ore-placer district. For their productivity ore-placer nodes are divided into the high (more than 50 ton of gold produced), medium (10-50 t) and low (less than 10 t) productive. The estimation of the nodes prospects for the ore and placer gold is given.